Overt disseminated intravascular coagulation and antithrombin III predict bleeding and in-hospital mortality in patients undergoing extracorporeal membrane oxygenation - Kim, Tae Wan; Ko, Ryoung-Eun; Choi, Ki Hong; Chung, Chi Ryang; Cho, Yang Hyun; Yang, Jeong Hoon (Frontiers in Medicine, 2024)
Background Limited data are available on the relationship of disseminated intravascular coagulation (DIC) with mortality in patients receiving extracorporeal membrane oxygenation (ECMO). Thus, we investigated the association of DIC score and antithrombin (AT) III with clinical outcomes in patients undergoing ECMO. Methods We analyzed 703 patients who underwent ECMO between January 2014 and May 2022 at Samsung Medical Center. The DIC score was calculated using laboratory findings within 24 hours of the ECMO initiation and ≥ 5 was defined as overt DIC. In addition, antithrombin (AT) III level was measured to identify the correlation with DIC score. Results Among the study patients, 169 (24.0%) were diagnosed with overt DIC (DIC group) during early maintenance therapy. In-hospital mortality was significantly higher in the DIC group than in the non-DIC group (55.0% vs. 36.5%, p < 0.001). Bleeding events were significantly higher in the group of patients with DIC score of 7 or 8 than in the other group (20.8% vs. 8.4%, p = 0.038). DIC score negatively correlated with AT Ⅲ level (r = -0.417, p < 0.001). The predictive performance of AT Ⅲ for overt DIC had statistical significance with a c-static of 0.81 (95% confidence interval (CI), 0.77-0.84, p < 0.001). Conclusion Overt DIC was associated with a higher in-hospital mortality and tendency of bleeding in ECMO patients. Furthermore, AT III plasma levels can easily predict overt DIC in patients undergoing ECMO. These findings suggest that monitoring AT III plasma levels may be important in the management of ECMO.